Pengaruh Pelatihan, Kompensasi, Disiplin Kerja dan Work-life Balance Terhadap Kinerja Karyawan PT Intidaya Dinamika Sejati Jember - Asma Nadzifah (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to determine the effect of training, compensation, work discipline, and work life balance on the performance of permanent employees of PT Intidaya Dinamika Sejati Jember. This study is motivated by the importance of effective human resource management in improving productivity and company performance. This study is a quantitative study with an explanatory or causality approach. The instrument used in this study was a questionnaire with a sample of 71 permanent employees of PT Intidaya Dinamika Sejati Jember. Data processing in this study used SPSS version 29. The results of the study showed that training had a significant effect on employee performance, compensation had a significant effect on employee performance, work discipline did not have a significant effect on employee performance, work life balance did not have a significant effect on employee performance, and training, compensation, work discipline, and work life balance simultaneously had a significant effect on employee performance.
Entry oleh Arif 2026 April 01
Keywords: Training; Compensation; Work Discipline; Work Life Balance; Employee Performance